Effects of tillage and crop residue management on runoff, soil loss and crop yield in the Humid Highlands of Ethiopia - Adimassu, Zenebe; Alemu, Getachew; Tamene, Lulseged D. (Elsevier, 2019)
This study was conducted on Eutric Nitisols of Holeta Agricultural Research Center (HARC) in the humid highlands of Ethiopia. The main objective was to assess the effect of tillage and crop residue management on runoff, soil loss and wheat (Triticum aestivum L.) yield over three years (2009–2011). Nine treatments combining three tillage practices (zero, minimum and conventional tillage) and three rates of crop residue (0, 1 and 2 t ha−1 yr−1) were used. The experiment was laid out in a Randomized Complete Block Design with three replications. The result showed that average runoff was significantly higher (332 mm) in zero tillage without crop residue (T0C0) and lower (198 mm) in conventional tillage with 2 t ha−1 yr−1 crop residue (T2C2). The average soil loss was lower (16 t ha−1 yr−1) in zero tillage with 2 t ha−1 yr−1 crop residue (T0C2) and higher (30 t ha−1 yr−1) in conventional tillage without crop residue (T2C0). Although, zero and minimum tillage treatments reduced soil loss significantly as compared with conventional tillage practices, the annual soil loss (16 t ha−1 yr−1) is still much higher than the tolerable soil loss for the Ethiopian highlands (2–10 t ha−1 yr−1). This suggests the need to complement zero and minimum tillage practices with physical soil and water conservation practices. On average, highest grain (2 t ha−1) and biomass (6 t ha−1) yields of wheat were recorded in T2C2 while the lowest grain and biomass yields were recorded in T0C0. Based on the above observation, we argue that conventional tillage combined with sufficient crop residue is the most appropriate approach to reduce runoff and increase wheat yield in the short-term. However, zero tillage practices with crop residue are effective to reduce soil loss. As this study was based on results of three years data, long-term study is needed to figure out the long-term impacts of tillage and crop residue management in Ethiopia.